Fases magnéticas de sistemas nanoestruturados de terras-raras - Sales, Fábio Henrique Silva (2011)
There is presently a worldwide interest in artificial magnetic systems which guide research activities in universities and companies. Thin films and multilayers have a central role, revealing new magnetic phases which often lead to breakthroughs and new technology standards, never thought otherwise. Surface and confinement effects cause large impact in the magnetic phases of magnetic materials with bulk spatially periodic patterns. New magnetic phases are expected to form in thin film thicknesses comparable to the length of the intrinsic bulk magnetic unit cell. Helimagnetic materials are prototypes in this respect, since the bulk magnetic phases consist in periodic patterns with the length of the helical pitch. In this thesis we study the magnetic phases of thin rare-earth films, with surfaces oriented along the (002) direction. The thesis includes the investigation of the magnetic phases of thin Dy and Ho films, as well as the thermal hysteresis cycles of Dy thin films. The investigation of the thermal hysteresis cycles of thin Dy films has been done in collaboration with the Laboratory of Magnetic Materials of the University of Texas, at Arlington. The theoretical modeling is based on a self-consistent theory developed by the Group of Magnetism of UFRN. Contributions from the first and second neighbors exchange energy, from the anisotropy energy and the Zeeman energy are calculated in a set of nonequivalent magnetic ions, and the equilibrium magnetic phases, from the Curie temperature up to the Nèel temperature, are determined in a self-consistent manner, resulting in a vanishing torque in the magnetic ions at all planes across the thin film. Our results reproduce the known isothermal and iso-field curves of bulk Dy and Ho, and the known spin-slip phases of Ho, and indicate that: (i) the confinement in thin films leads to a new magnetic phase, with alternate helicity, which leads to the measured thermal hysteresis of Dy ultrathin films, with thicknesses ranging from 4 nm to 16 nm; (ii) thin Dy films have anisotropy dominated surface lock-in phases, with alignment of surface spins along the anisotropy easy axis directions, similar to the known spin-slip phases of Ho ( which form in the bulk and are commensurate to the crystal lattice); and (iii) the confinement in thin films change considerably the spin-slip patterns of Ho.